Healthcare provider perceptions of the role of interprofessional care in access to and outcomes of primary care in an underserved area. Issue 2 (4th March 2018) - Wan, Shaowei; Teichman, Peter G; Latif, David; Boyd, Jennifer; Gupta, Rahul
ABSTRACT: To meet the needs of an aging population who often have multiple chronic conditions, interprofessional care is increasingly adopted by patient-centred medical homes and Accountable Care Organisations to improve patient care coordination and decrease costs in the United States, especially in underserved areas with primary care workforce shortages. In this cross-sectional survey across multiple clinical settings in an underserved area, healthcare providers perceived overall outcomes associated with interprofessional care teams as positive. This included healthcare providers' beliefs that interprofessional care teams improved patient outcomes, increased clinic efficiency, and enhanced care coordination and patient follow-up. Teams with primary care physician available each day were perceived as better able to coordinate care and follow up with patients ( p  = .031), while teams that included clinical pharmacists were perceived as preventing medication-associated problems ( p  < .0001). Healthcare providers perceived the interprofessional care model as a useful strategy to improve various outcomes across different clinical settings in the context of a shortage of primary care physicians.